Where the streets have a name: Income comparisons in the US - Abel Brodeur; Sarah Flèche (Institute for the Study of Labor (IZA), 2013)
This paper analyses how neighbors' income affect agents' well-being using unprecedented data from the BRFSS and the City of Somerville. We conduct a multi-scale approach at the county, ZIP code and street-levels and find that the association between well-being and neighbors' income follows an inverted U-shaped pattern in the size of the area. We find a negative relationship between well-being and neighbors' income in the county of residence, but the opposite at the ZIP code-level. Our results are consistent with the fact that agents enjoy living in a rich ZIP code but also having poor faraway neighbors since they have preferences for high social status. We test explicitly this interpretation by including amenities and the relative rank in the local income distribution in our model. At the street-level, we find a negative association between neighbors' income and self-reported well-being indicating the presence of income comparisons between very close neighbors.
Keywords: C25; D00; J31; 330; income comparisons; rank; relative utility; social interactions; social status; well-being